BUKHARA’S PARTICIPATION IN PUBLIC DIPLOMACY IN COOPERATION WITH FOREIGN COUNTRIES THROUGH UNIFIED CITIES - Tuyev Fazliddin Erkinovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
During the years of independence of Bukhara region cooperates with a number of countries in foreign relations. Buhari has established diplomatic relations with the United States, France, Turkey and States from foreign countries because of the “Unified cities” that have become closely friends.